Qualitative Longitudinal Research: From Monochrome to Technicolour. Issue 4 (19th October 2021) - Treanor, Morag C.; Patrick, Ruth; Wenham, Aniela
Abstract : Qualitative longitudinal research (QLR) has grown in prominence and popularity since the 2007 themed section on the subject in this journal. This new themed section reflects on how QLR has been mobilised and made sense of in recent times. This article showcases QLR's distinctive way of knowing and understanding the social world and how it can illuminate the processes through which policy can enhance, or indeed inhibit, the well-being of individuals and groups within society. This state of the art article focuses on QLR as a valuable but tricky approach. It argues that QLR can enhance qualitative research in social policy by fostering sustained policy engagement and development, and that this is especially useful for policy-making in relation to socioeconomic disadvantage. It also explores cross-cutting methodological dimensions pertinent to QLR's distinct approach, such as its enhanced ethical considerations, which are also integral to research with people at high risk of socioeconomic disadvantage. The article concludes with possible future directions and developments for QLR as a methodology.